Hyperlipidemia – The Hidden Link between Psoriasis and Cardiovascular Disease - Malik, Ahmed Naveed; Nadia Iftikhar; Muhammad Abbas; Anjum, Muhammad; Habib, Hunain; Minhas, Azhar Hosain (Pakistan Armed Forces Medical Journal, 2026)
Objective: To study the prevalence of dyslipidemia in patients of psoriasis and compare it with that of matched controls.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Dermatology, Pak Emirates Military Hospital (PEMH), Rawalpindi Pakistan, from Mar to Jun 2023.Methodology: The study enrolled 40 patients suffering from psoriasis and 40 healthy individuals considered as controls. Fasting Serum Total Cholesterol (TC), Serum Triglycerides (TG), Serum High Density Lipoprotein Cholesterol (HDL-C) and Serum Low Density Lipoprotein Cholesterol (LDL-C) of all the participants in both groups were measured and the results were compared and analyzed.Results: Out of the 40 patients of the psoriasis group, 27(67.5%) had at least one lipid abnormality while in the control group only 7(17.5%) individuals had aberrant fasting lipid profile. When both the groups were compared, there were significant differences in mean fasting serum concentrations of TG and HDL (p=0.001, p=0.001 respectively) as well as fasting serum concentrations of TC and LDL (p=0.001, p=0.001 respectively).Conclusion: Fasting lipid concentration was significantly abnormal for Serum Total Cholesterol (TC), Serum Triglycerides (TG), Serum High Density Lipoprotein Cholesterol (HDL-C) and Serum Low Density Lipoprotein Cholesterol (LDL-C), indicating a trend toward dyslipidemia in psoriasis patients.